Diagnóstico físico conservacionista e sua relação com a sedimentação e preferências da paisagem - Scapini, Gisele Patricia (2006)
The use and occupation of land have been occurred in an inadequated form many times in watersheds. Deforestations, farmings and fields planted in inadequate areas, in absence of Maintenancy treatments and urbanization without planning had been considered serious problems that generate ambient conflicts. These take to the environmental deterioration, soil erosion and natural landscapes depreciation. The Maintenancy Physical Diagnosis (MPD) is the most important ambient diagnostic since it has immediate and complete application in watersheds. It consists essentially in comparing the current use and the capacity of land use, having as a sample the watershed. The capacity of land use is determined through the ruggedness coefficient, which is obtained from the watershed relief and draining density. This type of environmental evaluation considers a better environmental life quality through a rational use of the physical, agricultural and urban space, with the pattern of available technician-scientific knowledge.The objective of this work had been to elaborate the MPD of Ibicuí-Mirim river watershed, to evaluate the use of the land in accordance with its natural vocation, aiming to identify the estimate of sedimentation and nevertheless analyze the landscape perceptions and preferences of the watershed in agreement with its use, thus to present adequate prognostics to the handling of the studied area. Through the MPD the potential use had been determined, conflicts of the land use, areas to plant trees, availability or excess of agriculture, areas that will be handled and found a deterioration of 33,31% in the watershed area. A susceptible sediment amount in order to be produced, of 38.866,74t/ano in the sediment had been evidenced, in the 1177,78 ha of total area. In relation to the landscape preference the methodology had been showed that the majority of people prefer the native forests landscapes, concluding thus, the importance of the MPD that in its essence indicates forestations to guarantee water infiltration, prevention of erosive episodes and in this way it guarantees natural landscapes that are most attractive for people.